Trends in the prevalence of thrombocytopenia among individuals iInfected with hepatitis C Virus in the United States, 1999-2008 - Kauf Teresa L; Nelson David R; Schelfhout Jonathan; Delaney Joseph AC; Wang Peter (BMC Research Notes, 2012)
Abstract Background Thrombocytopenia is associated with the natural history of hepatitis C virus (HCV) infection and anti-viral therapy. Recent, national estimates of the clinical burden of thrombocytopenia among HCV-infected individuals in the United States are unavailable. Bi-yearly data from the 1999-2000 to 2007-2008 National Health and Nutrition Examination Surveys (NHANES) were used to examine the prevalence of thrombocytopenia among HCV-infected individuals in the United States. Results Among 467 HCV-infected individuals in the survey (weighted population = 3,597,039), mean weighted age was 46.7 years (standard deviation = 15.5) and 61.7% were male. Overall, 7.6% met the study definition of TCP at the 150 × 109/L threshold; 4.5%, 2.0%, and 0.8% had platelet counts below 125, 100, and 75 × 109/L, respectively. The 2-year weighted prevalences of thrombocytopenia (150 × 109/L threshold) from 1999-2008 were 4.9%, 8.6%, 6.5%, 4.1%, and 12.9%. The unadjusted biannual time trend (odds ratio) was 1.16 (95% confidence interval = 0.82-1.64). In the two adjusted models, the odds by time ranged from 1.24-1.40, depending on whether the model included demographic or laboratory variables or both, but did not reach statistical significance. Age was positively and significantly related to thrombocytopenia status. Conclusions As the HCV-infected population ages, the prevalence of thrombocytopenia is expected to rise. This study provides limited evidence of such an effect at the national level.